Asupan zat besi, kadar hepsidin, dan kadar hemoglobin pada mahasiswi obesitas dan normal - Putri, Fonny Kurnia; Desmawati, Desmawati; Defrin, Defrin (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
Fe intake, hepcidin levels, and hemoglobin levels in obese and normal female studentsBackground: The most common anemia is related to problems with nutritional status. Obesity increases the risk of anemia because of the accumulation of fat in adipose tissue that triggers inflammation which can lead to anemia.Objective: This study aims to determine differences in iron (Fe) intake, hepcidin levels, and hemoglobin (Hb) levels in obese and normal female students.Methods: This research is an observational study with a comparative cross-sectional research design. Sampling was done by systematic random sampling. Data assessment of Fe intake, hepcidin levels, and Hb levels was carried out by SQ-FFQ interview, ELISA method, and cyanmethemoglobin method. Normality test and data analysis were performed using the Shapiro-Wilk test, independent t-test, Mann-Whitney, and Chi-Square.Results: The mean intake of Fe in obesity was 14.39±6.87 mg higher than the normal female students' 14.14±7.50 mg (p=0.726). The median hepcidin level in obesity was 322.32 pg/mL higher than normal female students 315.67 pg/mL (p=0.677). The mean hemoglobin level in obesity was 11,2±1,1 g/dL lower than normal female students 12,1±1,09 g/dL (p=0.001).Conclusions: There was no significant difference in Fe intake and hepcidin levels in the obese and normal female students. However, there was a significant difference in hemoglobin levels in obese and normal female students.